Changes in the cardiovascular profile in patients 3 and 12 months after COVID-19 pneumonia: parameters of arterial stiffness, global longitudinal strain, and diastolic function of the left ventricle - E. I. Yaroslavskaya; N. E. Shirokov; D. V. Krinochkin; A. V. Migacheva; I. O. Korovina; N. A. Osokina; A. D. Sapozhnikova; T. I. Petelina (Бюллетень сибирской медицины)
Aim. To study changes in the brachial – ankle pulse wave velocity (baPWV), ankle – brachial index (ABI), diastolic function, and global longitudinal strain of the left ventricle (LV) 3 and 12 months after COVID-19 pneumonia.Materials and methods. The dynamics of vascular age and LV global longitudinal strain was studied in 154 patients 3 and 12 months after COVID-19 pneumonia (51 ± 12 years, 48% were women). The control group consisted of 55 sexand age-matched individuals.Results. During the follow-up, the average baPWV decreased (13.2 [11.8; 15.1] cm / sec vs. 13.0 [11.8; 14.1] cm/ s; p < 0.001), and the frequency of its elevated values declined (45.4 vs. 35.1%; p = 0.008). The average ABI increased (1.09 [1.04; 1.14] vs. 1.11 [1.06; 1.17]; p = 0.012), but remained within the normal range. LV global longitudinal strain (LV GLS) (–19.6 ± 2.2 and –19.7 ± 2.5%; p = 0.854) and the frequency of reduced LV GLS (21.4 and 26.6%; p = 0.268) did not change significantly and did not differ from values in the control group. Global longitudinal strain in the LV basal inferoseptal segment improved (–19.2 ± 3.6% vs. –20.1 ± 4.0%; p = 0.032). The early diastolic mitral annular velocity decreased (8.4 ± 3.0 cm / s vs. 8.0 ± 2.5 cm / s; p = 0.023). The LV isovolumic relaxation time was greater than in the control group (101.8 ± 22.3 ms at the 1st visit vs. 92.9 ± 21.5 ms; p = 0.012; 105.9 ± 21.9 ms vs. 92.9 ± 21.5 ms at the 2nd visit; p < 0.001). A positive correlation was found between baPWV (r = 0.209; p = 0.009) and ABI (r = 0.190; p = 0.021) and strain parameters of the LV basal segments 12 months after discharge.Conclusion. Patients with optimal visualization on echocardiography at 12 months after COVID-19 pneumonia, compared to the results of the examination 3 months after the disease, had deteriorated parameters of LV diastolic function. LV GLS was within the grey zone and did not change significantly. An improvement in arterial stiffness was noted, associated with an improvement in the strain of basal LV segments.